Continuous applications of biochar to rice: Effects on grain yield and yield attributes - Min HUANG; Long FAN; Li-geng JIANG; Shu-ying YANG; Ying-bin ZOU; Norman Uphoff (Journal of Integrative Agriculture, 2019)
Biochar is considered as a beneficial soil amendment for crop production. However, limited information is available on the effects of continuous applications of biochar on rice. In this study, a fixed field experiment was conducted in the early and late rice-growing seasons from 2015 to 2017. Grain yield and yield attributes with a widely-grown rice cultivar Zhongzao 39 were compared, with and without applications of biochar in each season. The results showed that grain yield initially decreased with biochar applications in the first three seasons due to decreases in grain weight and harvest index. Although there were further relative decreases in grain weight and harvest index for rice that was supplied with biochar in the fourth to sixth seasons, grain yield was increased (by 4–10%) because of increases in sink size (spikelets per m2) and total biomass. The increased sink size in rice whose soil had been supplied with biochar in the fourth to sixth seasons was achieved by increasing panicle size (spikelets per panicle) or number of panicles, or both. Our study suggests that the positive effects of biochar application on rice yield and yield attributes depend on the duration of biochar application. Further investigations are needed to determine what are the soil and physiological processes for producing yield responses associated with ongoing applications of biochar. Also, it should be evaluated the performance of biochar application combined with other management practices, especially those can increase the grain weight and harvest index in rice production.